Interakcje sztuk plastycznych z językiem i literaturą na festiwalu Litery – słowo, litera, znak - Dobrzyńska, Teresa (Załącznik Kulturoznawczy, 2020)
The article reports on the events held as part of the ‘Letter Festival’, which was intended as an interdisciplinary project targeted at the graphic artists and painters as well as linguistic and literary scholars, poetry being one of the areas explored. The numerous visual works shown at the art exhibition explore the sign material – letters, words and a visual representations of concepts – in a variety of ways. My analysis of these works focuses on semiotic aspects (the indexical, iconic, and symbolic function of signs) and several analogies to phenomena under intense research by modern literary scholarship (intersemiotic metaphors, identity of the subject, narrative structures, intertextual relations, ironical revaluations of meanings).